Internalization of Sufi Values in Modern Education to Build Students' Mental Health - Fatimah, Riska Aulia Nurul; Rahman, Zidan Aulia; Affandi, Muhammad Gisan Jauhar; Hakim, Lukmanul; Selamet, Selamet (Halaqa: Islamic Education Journal, 2025)
The research examines the integration of Sufi principles into modern education to enhance students' mental health. It talks about how people are becoming more and more worried about students' mental health issues, like stress, anxiety, and depression, which can be made worse by schoolwork and cultural expectations. This study explains the potential of Sufi principles, such as patience, humility, self-control, and remembrance of God (dhikr), in nurturing emotional well-being and providing a holistic approach to mental health. Sufism emphasizes inner peace, the practice of ethics, and spiritual development, which complement cognitive-based education systems that often neglect emotional and spiritual health. The research employed a literature review methodology to examine recent studies concerning Sufism, mental health, and education. The findings indicate that Sufi practices such as mindfulness and self-reflection can alleviate anxiety and regulate emotions. By incorporating these principles into school culture and curriculum, students can learn to handle problems better, become more emotionally intelligent, and develop better attitudes. This study shows that integrating Sufi principles into education can enhance the learning environment, foster student support and satisfaction, and help address academic and mental health challenges. This means that future teaching methods should include the spiritual side of students' well-being, which will help them grow in all areas, including their minds, emotions, and spirits. This method could change how schools work now to improve the mental health of all the students. Highlights: Dhikr- and muraqabah-oriented contemplative practice aligns with mindfulness and is associated with reduced anxiety and better emotion regulation. Embedding spiritual–ethical principles within the curriculum and institutional ethos is linked to stronger coping capacity, emotional intelligence, and constructive attitudes. A synthesized framework connects Islamic spirituality with contemporary psychological techniques and clarifies educator–family–environment roles in implementation. Keywords: Internalization, Sufi Values, Modern Education, Mental Health, Students